Comparing perception of signals in different modalities during the cycling task: A field study. (August 2020) - Erdei, Elke-Henriette; Steinmann, Jochen; Hagemeister, Carmen
Highlights: Modality-dependent signal perception was analyzed in a naturalistic cycling setting. Participants responded significantly less often to visual signals than to both other signal types. Participants responded to only 65.1% of the transmitted visual signals. The response rates to auditory and tactile signals are similar except on bumpy roads. The environment within which the signal is transmitted affects signal perception. Abstract: Cyclists are considered to be amongst the most vulnerable road users and the number of cyclists involved in crashes is increasing. One possibility to improve bicycle safety is the implementation of assistance systems, for instance by providing the information needed to avoid critical situations. However, it is not known how and what kind of signals can reliably be transmitted to cyclists, in particular as warnings. This study has the objective to investigate which signal type dependent of the modality and the route type can be perceived during the cycling task. Therefore, we conducted a semi-naturalistic cycling study with 56 participants where a 10 km long, pre-defined route was individually cycled while 36 signals (visual, auditory and vibro-tactile) were transmitted. The participants signalled the perception of a signal by pressing a button. Response rates differed significantly between signal modalities. While auditory signals performed best closely followed by vibro-tactile signals, visual signals were frequently missed. The route type had an effect on the perception of the signals. The influence of the route segments with haptic interference was not expected to be this large on the perception of vibro-tactile signals. The obtained results indicate how and in which situations the different modalities are suited to transmit information to cyclists.